Drug-Induced Gingival Enlargement- A Practical Insight Into its Etiopathogenesis and Management - Lamichhane, Simant; Humagain, Manoj; Rupakhety, Prakriti; Rijal, Arjun Hari; Adhikari, Bhojraj (Birat Journal of Health Sciences, 2023)
Drug-induced gingival enlargements are a familiar finding in a dental setup. They are seen especially in the patient on anti-convulsant, immunosuppressive, and calcium channel blockers therapy. Amlodipine used primarily as a monotherapy or in combination therapy in the management of a trailing disease like hypertension is associated with gingival enlargement constantly. This case report unveils the management of amlodipine-induced gingival enlargement and accentuates the important considerations regarding etiopathogenesis and practical ways of managing the case on a daily basis.